The development of student online activity system for Pusat Kegiatan Pelajar, UiTM Malaysia / Nor Madiha Hassan - Hassan, Nor Madiha (2008)
Nowadays, information system has been very important to any organization in order to manage and maintain the data. Information system is not only used for learning and teaching but, also used in management and administration task such as record the information and so on. In Pusat Kegiatan Pelajar (PKP), there is no computerized system that can ease the staff to manage the data efficiently. All the tasks have been done manually. All the data regarding the student activity and society information have been kept in the filing system.